Hubungan Usia Menarche dengan Indeks Massa Tubuh pada Mahasiswi Fakultas Kedokteran Universitas YARSI Angkatan 2013 dan 2014 - Anisa Fikriani; Qomariyah Qomariyah (Majalah Sainstekes, 2018)
Girls who undergo early menarche have excess body weight and heightcompared to that experienced normal menarche or late. The prevalenceof early menarche in Indonesia in 2010 was 20,9%. Research conductedby Hyun Ju et al, showed that early menarche is a risk factor for obesityin adulthood. This study aims to investigate the relationship between ageof menarche with body mass index (BMI) at the Faculty of Medicinestudent YARSI force from 2013 to 2014 involving 87 female studentswere willing to become respondents to fill out questionnaires that havebeen provided as well as measuring the height and weight, researchconducted in YARSI in 2016 with cross sectional research methods. Theresults of statistical calculation using the Pearson chi-square test showedthe p value of 0.000 (P value less than 0.005), which means h0 rejected, thisproves that there is a relationship between the age of menarche withbody mass index in the student of the Faculty of Medicine YARSI force in2013 and 2014. Obesity is a risk factor in children who undergo earlymenarche therefore girls who undergo early menarche should maintain anutritionally balanced diet and exercise regularly.